Effects of Opisthorchis viverrini infection on glucose and lipid profiles in human hosts: A cross-sectional and prospective follow-up study from Thailand - Muthukumar, Radhakrishnan; Suttiprapa, Sutas; Mairiang, Eimorn; Kessomboon, Pattapong; Laha, Thewarach; Smith, John F.; Sripa, Banchob (Parasitology international, 2020)
Opisthorchis viverrini (OV) infection is endemic to the Northeast Thailand where the prevalence of Type 2 Diabetes mellitus (T2DM) is higher whilst the incidence of cardiovascular diseases (CVDs) is lower than the rest of Thailand. Helminth infection has both nutritional and immunological impact on their definitive hosts. Thus, a cross-sectional study was performed to see the effects of OV infection on glucose and lipid profiles. For this purpose, 200 each of OV infected and uninfected residents were recruited and their glycated hemoglobin (HbA1c), total cholesterol, triglycerides, low- and high-density lipoproteins (LDL and HDL) levels and anthropometric measurements, including BMI were examined. Then, as the prospective follow- up study, changes of those metabolic parameters of OV positive subjects (n = 120) before and after Praziquantel (PZQ) treatment were monitored for six months. The results showed that OV infection has a protective effect against hyperglycemia (OR 0.482 and p = .04) and metabolic disease risk group (OR 0.478 and p = .03). OV positive participants had lower HbA1c (5.5% Vs. 6.01%, p = .001) but higher HDL (54.07 Vs. 49.46 mg/dL, p = .001) than OV negative participants that are statistically significant. After PZQ treatment for OV-positive subjects, their serum levels of HbA1c (p < .05) and HDL (p < .05) significantly rose during the follow up. Apparently, OV infection lowers HbA1c but increases HDL in definitive human hosts. [Display omitted] •We compared glucose and lipid profile of Opisthorchis viverrini (OV) positive and negative participants.•OV positive participants had significantly lower HbA1c and higher HDL than OV negative participants.•Treating OV infection with PZQ lead to significant rise in HbA1c and HDL during six months follow-up•OV infection may affect glucose and lipid metabolism in definitive human hosts.